Morocco : Financial Sector Assessment Program: Technical Note-Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2016)
This paper describes mainly the introduction and performance of the Extended Fund Facility program for Pakistan. Since the start of the program in September 2013, economic growth has gradually recovered, inflation has fallen to low single digits, foreign reserve buffers have been rebuilt, social safety nets have been strengthened, and the fiscal deficit has significantly declined (although public debt remains high). Despite setbacks in privatization earlier in the year due to labor unrest and political opposition, the authorities remain committed to returning ailing public sector enterprises to a sound financial position, including through private participation, and to completing energy sector reform.